(untitled) (PANGEEA, 2025)
ABSTRACT: Mures River is the largest river and flows through the interior of Romania, from east to west around the Transylvanian Depression. Big rises in Mount Hasmasul Mare and flows into the Tisza, in Hungary. The paper highlights the main features of the river: water supply, seasoning drainage, annual average flows, in the middle sector.